Analisis Yuridis terhadap Peran Badan Penyelesaian Sengketa Konsumen dalam Perlindungan Konsumen di Indonesia - SARI, MAULIDINA; YOE, AVECIENA; WINDARTO, WINDARTO (Fakultas Hukum Universitas Riau, 2025)
This paper aims to evaluate the performance of non-judicial consumer dispute resolution institutions in fulfilling their role as protectors of consumer rights, particularly in light of the growing complexity of contemporary commercial transactions and the proliferation of sector-specific dispute resolution forums. The primary focus of this study is to assess the extent to which these institutions are capable of delivering legal protection that is effective, expedient, and accessible, despite facing various structural and functional limitations such as unclear jurisdictional boundaries, overlapping mandates with other bodies, and weak institutional infrastructure. The research adopts a normative juridical approach, employing doctrinal legal analysis and the examination of relevant case decisions. The findings reveal that, structurally, these institutions continue to encounter fundamental challenges, including the limited binding effect of their decisions, which remain subject to judicial review, the lack of regulatory coherence, and insufficient institutional capacity particularly in addressing disputes arising from digital transactions and financial services. The absence of a uniform national procedural standard further contributes to inconsistencies in implementation across regions. This study underscores the urgent need to strengthen the institutional role through the harmonization of sectoral regulations, restructuring of institutional authority, and the development of an integrated digital complaint system. These findings are expected to contribute to the formulation of institutional policy frameworks that are more adaptive and effective in responding to the evolving challenges of consumer protection.